AKRAB EKSPLORASI ANGLE CAMERA DALAM PRODUKSI FEATURE “GIR PASANG” - Sujianti Hans Hermang Mintana M. Suparwoto (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTThis feature program entitled "Gir Pasang" which discusses a village named Gir Pasang located on the slopes of Mount Merapi, precisely Kemalang included in the subdistrict, Klaten, Central Java. Gir Pasang is extremely isolated because it is located between the steep ravines and away from the construction of infrastructure such as mosques, schools and health centers. This hamlet is also entered into the Merapi eruption disaster-prone areas. Even so, the villagers of Gir Pasang still choose to survive and stay in the village without worrying eruption of Mount Merapi since they mempercaya that they will remain safe if Mount Merapi erupts because there are mountains green which is believed to be older than the Mount Merapi that Mount Merapi dare not pass if the eruption. To establish friendships with Merapi, until now they preserve the tradition selametan as a symbol of friendship. Creating the works feature in desperately needed a photographer to take pictures as directed by the Director.This program focuses on the exploration of camera angle in the delivery of information visually. The camera angle used is eye-level, high angle, low angle and bird eyes. In addition, using the technique cameraman panning camera movement, tracking, tilting, crabbing and following. As for the type of shot that is used among close-up, medium close-up, medium shot, medium long shot, long shot, and the full shot. All camera techniques used in order to produce images yabg vary so it is not boring. In addition, to produce an image of a dynamic, dramatic, expressive and have the information.Keywords: feature, gir pasang, angle exploration